2021
DOI: 10.1093/ntr/ntab115
|View full text |Cite
|
Sign up to set email alerts
|

Longer-Term Impact of the Flavored Tobacco Restriction in Two Massachusetts Communities: A Mixed-Methods Study

Abstract: Introduction In response to high rates of youth tobacco use, many states and localities are considering regulations on flavored tobacco products. The purpose of this study was to assess whether flavored tobacco restrictions (FTRs) in Massachusetts curb youth tobacco use over time, and whether a dose-response effect of length of policy implementation on tobacco-related outcomes exists. Methods Using a quasi-experimental design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Again using DiD, Kingsley et al [ 40 ] evaluated the impact of flavoured tobacco restrictions on high school student tobacco use in the cities of Salem and Attleboro compared to Gloucester, MA. They report that ever and current use of flavoured and non-flavoured or menthol tobacco increased in all three cities from baseline to follow-up, but current use of flavoured and non-flavoured or menthol tobacco was significantly smaller in adopting municipalities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again using DiD, Kingsley et al [ 40 ] evaluated the impact of flavoured tobacco restrictions on high school student tobacco use in the cities of Salem and Attleboro compared to Gloucester, MA. They report that ever and current use of flavoured and non-flavoured or menthol tobacco increased in all three cities from baseline to follow-up, but current use of flavoured and non-flavoured or menthol tobacco was significantly smaller in adopting municipalities.…”
Section: Resultsmentioning
confidence: 99%
“…They report that ever and current use of flavoured and non-flavoured or menthol tobacco increased in all three cities from baseline to follow-up, but current use of flavoured and non-flavoured or menthol tobacco was significantly smaller in adopting municipalities. They also conducted focus groups where some respondents discussed leaving the county or state to purchase products [ 40 ]. Olsen et al [ 41 ] found similar effects in Minnesota, where any tobacco product use among youths remained flat following the 2016 ban on any flavoured products in Minneapolis and St. Paul but rose in the rest of the state.…”
Section: Resultsmentioning
confidence: 99%
“…These reductions stand in stark contrast to the limited decreases observed in New Jersey, where only menthol-flavored e-cigarettes decreased. The differences observed further illustrate the importance of comprehensive flavor laws in the near term that can lead to decreases in youth use one to two years post implementation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the potential impact of ESRs, especially flavoured ESRs, among localities and states, an increased number of research studies were conducted. These studies mainly examined the retail sales data for e-cigarette products9–12 in the localities of interest (or in comparison with similar or adjacent localities) or assessed individuals’ tobacco use behaviour data to examine the change of current or recent e-cigarette use cross-sectionally at one or multiple points in time 13–16. Specifically, studies using e-cigarette retail sales data most consistently found an impact of flavoured ESRs on reducing retail sales of e-cigarette products 9–12.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, adult e-cigarette users who also smoke cigarettes may be less likely to be influenced by ESR policies than e-cigarette users who are non-smokers 18 19. Lastly, almost all previous research examining the impact of ESRs or flavoured ESRs was conducted before the COVID-19 pandemic 9–15. Evidence has shown that the pandemic may disrupt local public health policy enforcement20 21 and retailer compliance with local tobacco control measures22 23 as well as change individuals’ tobacco-related consumption and purchasing behaviours 24–26.…”
Section: Introductionmentioning
confidence: 99%